Fatigue Correstion Behavious of AISI 304 Stainles Steel in 3.5% NaCl Solution - Herdi Susanto; M. Ridha; Syifaul Huzni (Syiah Kuala University, 2012)
Failuredue to corrosion fatigue is a phenomenon that often occurs in thestructure associated with a corrosive environment. Stepuse ofmaterialssuch as AISI 304 stainlesshas been done, buta failuredue to corrosion fatigue phenomena still occur and can not be understood and explained by the experts. This study focused on assessing changes in behaviorof AISI 304stainless steelareexperiencingrepeatedloadingincorrosive environment. The behavior changes observed with fatigue testing in laboratory air and 3.5% NaCl solution, using a fatigue testing machine typerotary bending, specimens weremadeaccording to ASTME-466 andASTMF-1801 for corrosionfatiguetesting.Fatigue testing presented in S-Ncurve and fracture patterns observed, observed in3.5% NaCl solution and constantstress 369.53 MP apitgrowth measurements done on sevenl evels and four levels of cycles for corrosion potential and current measurements a represented in the polarizationcurve. The results showe dthat the endurance limit of the laboratoryair environment at stress 323.34MPa and 3.5% NaCl solution decreases, up to stress 277.15 MPa at1.7x107cycles. Ductile fracture pattern is in the airand 3.5% NaCl solutionis brittle. Pits and cracks growth, failure is dominated by crack propagation and increase the number of cycles resulting in decreased surface potential and corrosion current density increases.